Curricular materials according to the Organic Act of Education 2006. An outlook from Valencia - Oltra Llini, Ferran; Carbonell García, Ignacio (Avances en Supervisión Educativa, 2007)
By Ferran Oltra Llin and Ignasi Carbonell García, teachers and curricular material authors.Curricular materials have the purpose of helping teachers to go from the curriculum decree of Mininal Teaching to the School Project and the classroom teaching schedule.Text-books are, among the collection of varied curricular material, the most widely used carrier to show the contents on which many of school activities are carried out.